Consulting report - Bigmond Knowledge Center implementation plan - Hurtado Esquerre, Alexandra Beatriz (2019)
Located in the capital of Peru, Bigmond is a service company that is dedicated to the search for top executives and provides human resources consulting, as well as other complementary services. Currently, the company faces increasingly growing competition in the market, there are renowned competitors and new competitors, and a slow appearance of Think Tanks in Peru. That is why the company is interested in developing a Knowledge Center, which seeks to give Bigmond the differentiation it requires at the moment and finish positioning its brand in the market. The reputation of companies, in this industry, is necessary to increase their client portfolio, so the company aims to be not only a company that generates economic value for its investors, but also to be a company that contributes to the development of the community. To achieve the objective of implementing a Knowledge Center for Bigmond, it began by knowing the external and internal factors that could affect the company, and Porter's five forces were used to analyze the industry. Then. sources were reviewed on what it implied to develop a Knowledge Center and those that already existed in Peru. Then, a quantitative and qualitative analysis was performed to determine what things have to be taken into account for implementing a Knowledge Center. The result of this research defined the role model, which will place this Knowledge Center as a new area of the company (Research and Development), but it will have an independent marketing campaign for the company, as well as income generation for financing. Finally, the result of this implementation results in Bigmond increasing its client portfolio, its sales, its reputation, visits to its website. On the other hand, the expected results for this new area are to generate publications that are useful for business and that are referenced in other studies. For all this, this project helps to get Bigmond's interests.